An integrated reduced order model considering degradation effects for LiFePO4/graphite cells. (1st August 2018) - Zhao, Xinchen; Bi, Yalan; Choe, Song-Yul; Kim, Soo-Yeol
Abstract: A reduced order model (ROM) considering degradation effects is proposed and validated against experiments for both fresh and cycled lithium iron phosphate (LFP)/graphite cells. The ion behaviors in the LFP particles such as two-phase transition and path dependence are modeled using a shrinking core with a moving interface between a lithium-rich and a lithium-deficient phase. The model errors are further minimized by employing the Extended Kalman Filter (EKF) to achieve a more accurate state-of-charge (SoC) estimation. The average error of SoC and voltage estimation is kept within 4% and 2%, respectively. Side reaction is regarded as the predominant cause of degradation, which can be accelerated by elevated temperatures, high SoC levels and large SoC cycling limits. The effects of operating conditions on degradation are described by a modified Butler-Volmer equation that is incorporated into the developed ROM. The integrated model facilitates to represent the degradation effects of side reaction, including loss of ions, loss of active material, growth of solid electrolyte interphase and deposit layer, and electrolyte decomposition. The model is capable of estimating capacity and power with an accuracy of 2% and 3% up to 1000 cycles, respectively.